Fate and transport of petroleum hydrocarbons in engineered biopiles in polar regions. (July 2015) - Whelan, M.J.; Coulon, F.; Hince, G.; Rayner, J.; McWatters, R.; Spedding, T.; Snape, I.
Highlights: We account for temperature-dependency of partitioning and degradation of hydrocarbons. We derived the energy of activation ( Ea ) for the degradation of various hydrocarbon fractions. We examine the changes of hydrocarbons fractions within five field scale biopiles in Antarctica. As Ea increases the percentage of TPH remaining increases, reflecting slower biodegradation. Despite low temperature, the predicted dominant loss process is biodegradation. Abstract: A dynamic multi-media model that includes temperature-dependency for partitioning and degradation was developed to predict the behaviour of petroleum hydrocarbons during biopiling at low temperature. The activation energy ( Ea ) for degradation was derived by fitting the Arrhenius equation to hydrocarbon concentrations from temperature-controlled soil mesocosms contaminated with crude oil and diesel. The model was then applied to field-scale biopiles containing soil contaminated with diesel and kerosene at Casey Station, Antarctica. Temporal changes of total petroleum hydrocarbons (TPH) concentrations were very well described and predictions for individual hydrocarbon fractions were generally acceptable (disparity between measured and predicted concentrations was less than a factor two for most fractions). Biodegradation was predicted to be the dominant loss mechanism for all but the lightest aliphatic fractions, for which volatilisation was most important. Summertime losses were significant, resulting in TPH concentrations which were about 25% of initial concentrations just 1 year after the start of treatment. This contrasts with the slow rates often reported for hydrocarbons in situ and suggests that relatively simple remediation techniques can be effective even in Antarctica.